Desarrollo de un modelo multicriterio para la selección y priorización de criterios para proyectos de voluntariado global en Colombia (2020)
AIESEC is a non-profit organization, located in more than 128 countries and has approximately 25,000 members, its main objective is to contribute to the development of each of the countries where it is located, supporting social causes and generating new projects focused on the Sdgs (Sustainable Development Goals), the research project "DEVELOPMENT OF A MULTI-CRITERIA MODEL FOR THE SELECTION AND PRIORITIZATION OF CRITERIA FOR GLOBAL VOLUNTEERING PROJECTS IN COLOMBIA", was created under the need and background presented by AIESEC in Colombia to implement a tool to their processes that provides them with better quality in the selection of volunteers. This project was designed thanks to the help of the incoming National Director of Global Volunteering of the national office at AIESEC in Colombia, the vice presidents of the period 2018-2019 and 2019-2020 of the different committees, who offered their support in the process of identifying problems and helped us to feed back the process through their contributions focused on the initial objective of providing a process with a higher response rate and certainty. The model has been proposed for AIESEC in Colombia, which has its domicile of the national office in the city of Bogotá D.C, on Calle 37 # 25-09, where the project was monitored from July 25, 2019 to May 5, 2020.